2019
DOI: 10.1096/fasebj.2019.33.1_supplement.562.5
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Action Potential Discharge in Human Muscle Sympathetic Nerve Activity

Abstract: Pulse‐rhythmic bursts formed by synchronous action potential (AP) discharge characterises the firing behaviour of muscle sympathetic nerve activity (MSNA). However, complex AP discharge patterns related to multiple sites of control warrant an investigation of synchronicity in the human sympathetic system. Therefore, this study quantified the synchronicity of muscle sympathetic AP discharge in eight healthy individuals (4 females, 23 – 31 years, 170 ± 7 cm, 69 ± 13 kg, 60 ± 7 bpm, 89 ± 6 mmHg). MSNA (microneuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…4E). APs exhibiting asynchronous discharge activity between pulse-synchronous bursts is in agreement with the results from Klassen et al, who suggested that reduced percentage of asynchronous APs during orthostatic and apnoeic stress may be reflective of one and/or two phenomena (Klassen et al, 2019). The first theory is the existence of an active AP synchronization mechanism.…”
Section: Sympathetic Discharge Patterns In Response To Hypoxiasupporting
confidence: 91%
See 4 more Smart Citations
“…4E). APs exhibiting asynchronous discharge activity between pulse-synchronous bursts is in agreement with the results from Klassen et al, who suggested that reduced percentage of asynchronous APs during orthostatic and apnoeic stress may be reflective of one and/or two phenomena (Klassen et al, 2019). The first theory is the existence of an active AP synchronization mechanism.…”
Section: Sympathetic Discharge Patterns In Response To Hypoxiasupporting
confidence: 91%
“…1C. Previous findings from Klassen et al (2019) suggest that a considerable number of APs discharge asynchronously between sympathetic bursts. Therefore, any detected AP during baseline, hypoxia and recovery was extracted regardless of whether it occurred within an identified MSNA burst or not.…”
Section: Action Potential Detection and Analysismentioning
confidence: 91%
See 3 more Smart Citations